A Hybrid Methodology for Performance Assessment of Campus Network - Li Mao; De-yu Qi (Institute of Advanced Engineering and Science, 2015)
In this paper, we propose a combined methodology of fuzzy analytic hierarchy process (FAHP) and data envelopment analysis (DEA) in order to apply it to multivariate analysis and integrated evaluation. With FAHP method, the relative importance levels of different available indicators are determined. And the DEA model is used to obtain the efficiency performances of the use case of network measurement. Finally network performance is evaluated by means of integrating available indicator weights with efficiency performances. It is quite important that the integrated methodology considers both personal preferences and objective relative efficiency for assessment simultaneously to avoid the bias of single methodology.